EP-631 Left Ovarian Teratoma Containing Follicular Thyroid Carcinoma: A case Report. (9th August 2022) - Rezkallah, Emad; Elsaify, Wael
Abstract: Introduction: A mature cystic teratoma of the ovary is composed of well-differentiated derivatives of the three germ layers, the ectoderm, the mesoderm and the endoderm. About 20% of ovarian teratomas contain thyroid tissues. When thyroid tissue comprises more than 50% of the ovarian teratoma, it is termed; struma ovarii. Patients are usually asymptomatic or predominantly presented with a pelvic mass in 45% of cases or abdominal pain. We represent a rare case of stuma ovarii containing follicular thyroid carcinoma. Case presentation: A 56 years old patient presented with a left ovarian mass. The patient had no history of any thyroid abnormalities and no family history of thyroid malignancy. The patient underwent total hysterectomy (TH) and bilateral salpingo-oophrectomy (BSO). Mature cystic teratoma of the left ovary containing highly differentiated follicular carcinoma with omental deposits was discovered. The case was referred for thyroid MDT for discussion of further management. Thyroid US and CT scans showed slightly small thyroid containing multiple hypoechoic nodules with no evidence of distant metastasis. Management: The patient had total thyroidectomy and the final histopathology reported incidental multifocal papillary microcarcinomas of follicular variant; stage pT1a. Post-operatively the patient had Radio-iodine ablation. TSH suppression with thyroxin was initiated. The patient had regular radiological and thyroglobulin checks and no recurrence was detected on 5 years of follow-up. Conclusion: The treatment for malignant struma ovarii depends on the tumor stage. The initial surgery includes TH and BSO with omentectomy. The adjuvant treatment includes thyroxine, total thyroidectomy with RAI ablation. Long-term follow-up is recommended.